RETRACTED: PRESERVATION POTENTIAL OF COMBINATION OF CLOVE AND LEMON BASIL ESSENTIAL OILS ON FRESH CHICKEN MEAT - Dwi Hartanti; Nur Annisa Septiyaningrum; Alwani Hamad (Indonesian Food and Nutrition Progress, 2019)
We found this paper already published in the Journal of Food Quality and Hazards Control 2020: 7 (2): 84-93 with the title "Combination of Clove and Lemon Basil Essential Oils for Preservation of Chicken Meat". http://jfqhc.ssu.ac.ir/browse.php?a_code=A-10-852-1&slc_lang=en&sid=1 We retract the publication under the title "PRESERVATION POTENTIAL OF COMBINATION OF CLOVE AND LEMON BASIL ESSENTIAL OILS ON FRESH CHICKEN MEAT" Volume 16 No. 2 2019 http://dx.doi.org/10.22146/ifnp.50381 The document and its content will be removed from the Indonesian Food and Nutrition Progress journal.